Disaster risk reduction of Mount Kelud eruption based on capacity building: A case study in Kasembon District, Malang Regency - Dwi Rahmawati; Turniningtyas Ayu Rachmawati; Gunawan Prayitno (Sustinere: Journal of Environment and Sustainability, 2018)
The ability to respond to and recover from disasters is highly dependent on a community’s capacity. This study assessed the capacity level of the community in Kasembon District, an area affected by the Mount Kelud eruption in 2014. The capacity level assessment was conducted by identifying pentagon asset components, which include human capital, social capital, financial capital, natural capital, and physical capital. Bayem is a village with a medium capacity level despite having low levels of natural, financial, and physical capital. However, this deficiency is compensated by the active participation of the community within the village organization. Pondok Agung, Kasembon, Sukosari, and Pait are four villages with similar conditions to Bayem, but the level of community involvement is not as active as in Bayem. Based on the research findings, villages with strong social engagement tend to have a higher capacity to respond to and recover from disasters.